Relationship of Self-Efficacy and Obstacles of E-Learning Towards Online Method in IR4. 0 - Ahmad Nur Aizat, Ahmad; Md Fauzi, Ahmad; Norhadilah, Abdul Hamid; Abdul Talib, Bon; Raja Zuraidah, Rasi; Nawanir, Gusman; Adnan, Bakri; Mustaqqim, Abdul Rahim (Review of International Geographical Education, 2021)
In IR4.0 situation, online method and e-learning been considered as a part to be implemented. Self-efficacy and obstacles in e-learning are the elements to be concerned in the learning process. The ultimate objective of this research is to identify self-efficacy and obstacles in e-learning experienced by students. Further, this research determines the relationships among self-efficacy and obstacles in e-learning. There are 202 students in year 2 and year 3 in Faculty of Technology Management and Business (FPTP) were chosen as respondents of this study. Self-efficacy refers to how confident an individual feels about handling particular tasks, challenges and context given by the lecturer. Obstacles were defined as the resistance faced by students that bringing negative effects to them in using e-how. This research used questionnaires and quantitative methods for data collection method. The relationships among self-efficacy in e-learning and obstacles in e-learning is very weak. This research has been carried out to accomplish the objectives set by the researchers to identify the self-efficacy in using e-learning and obstacles in e-learning. The findings show that the students have e-learning self-efficacy (mean= 3.8201). Four elements of obstacles (factors) emerged, that include personality, organization, situational and technological obstacles. Organizational obstacles were the most prevalent (mean= 3.3020), followed by personality obstacles (mean= 3.2855), and situation obstacles (mean= 3.281). Technology obstacles (mean= 2.7723) were the least common. To conclude the research for identifying the relationship between self-efficacy and obstacles in e-learning experience, one hypothesis was tested and accepted.